2010
DOI: 10.4067/s0718-16202010000100007
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal effect of six commercial extracts of Chilean propolis on Candida spp

Abstract: The antifungal effect of six commercial extracts of Chilean propolis on Candida spp. Cien. Inv. Agr. 37(1): 75-84. Propolis has been used in traditional medicine for many centuries because of its beneficial health properties, including its antimicrobial capacity. Prosthesis stomatitis affects a significant percentage of users of removable dentures; Candida albicans is the most common fungal species associated with the development of this pathology. Thus, the objectives of this study were: a. To evaluate the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
3
29
0
9
Order By: Relevance
“…The total polyphenol and flavonoid concentrations are similar to those reported by Vidal et al (2009) and Herrera et al (2010) who also evaluated Chilean commercial ethanol extracts of propolis and were similar to those reported in samples of Argentine (Bedascarrasbure et al, 2004Chaillou and Nazareno, 2009) and Brazilian propolis (Castro et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The total polyphenol and flavonoid concentrations are similar to those reported by Vidal et al (2009) and Herrera et al (2010) who also evaluated Chilean commercial ethanol extracts of propolis and were similar to those reported in samples of Argentine (Bedascarrasbure et al, 2004Chaillou and Nazareno, 2009) and Brazilian propolis (Castro et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…Numerous studies have demonstrated the versatile pharmacological activities of propolis, including antibacterial, antifungal, antiviral, antiinflammatory, hepatoprotective, antioxidant, and antitumor properties (Hegazi and Abd El Hady, 2002;Tolosa and Cañizares, 2002;Castagna et al, 2004;Garedew et al, 2004;Popova et al, 2005;Quintero-Mora et al, 2008;Popova et al, 2009;Herrera et al, 2010;Saavedra et al, 2011). The control of phytopathogenic fungi by propolis has been proposed by Hegazi and Abd El Hady (2002) who evaluated the use of Egyptian propolis to control nine postharvest fungi and reported successful inhibition of the fungi, with minimum inhibitory concentration values ranging between 1.2-3.6 mg mL .…”
Section: Introductionmentioning
confidence: 99%
“…Al término de la incubación se traspasó 10 µL de cada tubo a placas de agar sabouroud utilizando un asa calibrada, realizando la técnica de sembrado por agotamiento (Herrera, 2010), posteriormente se incubo durante 24, 48 y 72 horas a temperatura ambiente, al término de este tiempo se realizó inspección visual de cada placa. La CMI se determinó como la concentración mínima de extracto etanólico de propóleos donde no hubo crecimiento visible después del periodo de incubación [22].…”
Section: Determinación De La Concentración Mínima Inhibitoria (Cmi)unclassified
“…Entonces el propóleos puede vislumbrarse como potencial tratamiento contra las infecciones por hongos, tanto levaduriformes como filamentosos sobre la base del constante aumento de la prevalencia de las micosis, del desarrollo de resistencia a agentes antimicóticos actuales, de los efectos adversos que poseen estos antimicóticos y porque la terapia con propóleos resulta económica y poco tóxica (dosis diarias de 1.400 mg/kg no ocasiona efectos adversos en ratones, aunque el consumo bruto en el hombre puede generar náuseas), de allí la necesidad de realizar ensayos sobre su efecto antimicótico y también porque la composición química del propóleos aunque similar puede presentar pequeñas variaciones en distintas regiones del mundo que requieren ser precisadas [1]- [2]- [3]- [11]- [12]- [13]- [14].…”
Section: Introductionunclassified
“…Evaluations of the biological activity of propolis, particularly its antifungal activity, have been reported previously (Herrera et al, 2010). All propolis samples, independent of their source, present antimicrobial activity because this material must protect the hive (Buriol et al, 2009).…”
Section: Discussionmentioning
confidence: 99%